Histological and magnetic resonance imaging assessment of Liqoseal in a spinal in vivo pig model - Emma M. H. Slot; Wilhelmina Bergmann; Ahmet Kinaci; Bart deBoer; Nizar Moayeri; Saskia Redegeld; Sander vanThoor; Tristan P. C. vanDoormaal (Animal Models and Experimental Medicine, 2023)
Abstract Background Liqoseal (Polyganics, B.V.) is a dural sealant patch for preventing postoperative cerebrospinal fluid (CSF) leakage. It has been extensively tested preclinically and CE (Conformité Européenne) approved for human use after a first cranial in‐human study. However, the safety of Liqoseal for spinal application is still unknown. The aim of this study was to assess the safety of spinal Liqoseal application compared with cranial application using histology and magnetic resonance imaging characteristics. Methods Eight female Dutch Landrace pigs underwent laminectomy, durotomy with standard suturing and Liqoseal application. Three control animals underwent the same procedure without sealant application. The histological characteristics and imaging characteristics of animals with similar survival times were compared to data from a previous cranial porcine model. Results Similar foreign body reactions were observed in spinal and cranial dura. The foreign body reaction consisted of neutrophils and reactive fibroblasts in the first 3 days, changing to a chronic granulomatous inflammatory reaction with an increasing number of macrophages and lymphocytes and the formation of a fibroblast layer on the dura by day 7. Mean Liqoseal plus dura thickness reached a maximum of 1.2 mm (range 0.7–2.0 mm) at day 7. Conclusion The spinal dural histological reaction to Liqoseal during the first 7 days was similar to the cranial dural reaction. Liqoseal did not swell significantly in both application areas over time. Given the current lack of a safe and effective dural sealant for spinal application, we propose that an in‐human safety study of Liqoseal is the logical next step.